Integrated Database Design to Support the Development of Indonesian Seafarer Competency Information System - Wahyuni, Okvita; Kristiyanti, Mariana; Mahendro, Iwan; Khoriyatun, Siti (Politeknik Ilmu Pelayaran Semarang, 2025)
The Indonesian shipping industry has been greatly impacted by the advancement of information and technology, particularly with the introduction of the Integrated Information System (SIT), which facilitates more effective resource management for shipping businesses. Every manager and executor in the maritime industry must practice technical and structural management in order to strengthen maritime human resource capabilities and boost national competitiveness. By using SIT in the context of contemporary businesses, this study seeks to revitalize the Human Resource (HR) management database and enhance the competences of Indonesian sailors. The researchers investigate the efficacy, advantages, and difficulties of reviving an integrated database in human resource management by carrying out an extensive literature review. Interviews and a thorough analysis of numerous relevant information sources are part of the descriptive qualitative research methodology. According to the research findings, operational effectiveness, data-driven decision-making, and the general caliber of human resource services can all be improved by reviving seafarer competency development through the use of an integrated database design in seafarer human resource management. But there are still obstacles to overcome, such reluctance to change and concerns about data security. In order to enhance marine human resources, all stakeholders must work together to revitalize Indonesian sailors' competencies through an integrated database.